Bladder function after conservative surgery and high‐dose rate brachytherapy for bladder–prostate rhabdomyosarcoma. Issue 8 (19th January 2022) - Lobo, Sara; Gaze, Mark N.; Slater, Olga; Hoskin, Peter; Sands, Gordon; Sullivan, Tracy; Cho, Alexander; Eminowicz, Gemma; Smeulders, Naima
Abstract: Background: Conservative surgery (CS) brachytherapy (BT) techniques for local therapy in bladder–prostate rhabdomyosarcoma (BP‐RMS) seek to retain organ function. We report bladder function after high‐dose rate (HDR) BT combined with targeted CS for any vesical component of BP‐RMS. Procedure: Prospective cohort of all BP‐RMS patients between 2014 and 2019 receiving HDR‐BT (iridium‐192, 27.5 Gy in five fractions) with/without percutaneous endoscopic polypectomy (PEP) or partial cystectomy (PC). Functional assessment included frequency–volume chart, voided volumes, post‐void residual, flow studies, continence status and ultrasound scanning; abnormalities triggered video urodynamics. Results: Thirteen patients (10 male), aged 9 months to 4 years (median 23 months), presented with localised fusion‐negative embryonal BP‐RMS measuring 23–140 mm (median 43 mm) in cranio‐caudal extent. After induction chemotherapy, local treatment consisted of PC+BT in three, PEP+BT in four and BT alone in six. At a median 3.5 years (range 21 months to 7 years) follow‐up, all were alive without relapse. At a median age of 6 years (4–9 years), the median bladder capacity was 86% (47%–144%) of that expected for age, including 75% (74%–114%) after PC. Radiation dose to the bladder was associated with urinary urgency, but not bladder capacity or nocturnal enuresis. Complications occurred in two: one urethral stricture and one vesical decompensation in a patient with pre‐existing high‐grade vesico‐ureteric reflux (VUR). The remaining patients were dry by day; five with anticholinergic medication for urinary urgency. Three patients are enuretic. Conclusions: Day‐time dryness at a median 3.5 years after CS‐HDR‐BT was achieved in 92%, with 85% voiding urethrally, and 62% attaining day‐and‐night continence aged 4–9 years. We report reduced open surgery with minimally invasive percutaneous surgery, with HDR‐BT or BT alone being suitable for many.